2009
DOI: 10.1007/s12237-009-9198-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Phytoplankton Dynamics in Harima-Nada, Eastern Seto Inland Sea, Japan During a 35-Year Period from 1973 to 2007

Abstract: Long-term monitoring of water quality and phytoplankton was conducted at 19 sampling stations in Harima-Nada, eastern Seto Inland Sea, Japan for 35 years from 1973 to 2007. There were two significant long-term changes, an increase in winter water temperatures of 0.042°C year −1 , and a decrease in dissolved inorganic nitrogen (DIN) from about 10 μM in the 1970s to~5 μM in the late 1990s due to the reduction in nutrient inputs. DIN concentrations and total phytoplankton cell density were both higher during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…Nishikawa et al (2010) reported that there were two significant long-term changes, i.e. an increase in water temperature of 0.042°C year…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nishikawa et al (2010) reported that there were two significant long-term changes, i.e. an increase in water temperature of 0.042°C year…”
Section: Discussionmentioning
confidence: 99%
“…In Harima-Nada, the Fisheries Technology Institute, Hyogo Prefectural Technology Center for Agriculture, Forestry and Fisheries, initiated measuring of water quality parameters in April 1973, along with the identification and cell counts of phytoplankton to monitor the fishing grounds (Manabe et al 1994, Nishikawa et al 2010. The monitoring has been carried out using similar methods until now, therefore, the data sets allow evaluation of eutrophication and recovery processes in Harima-Nada (Nishikawa et al 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations